Exploring the Relationship between Preservice Preschool Teachers’ Views about the Teacher Effectiveness Training Model and Their Communication Skills - Sak, İkbal Tuba Şahin; Kardeş, Servet; Mahmood, Sairan Mohammed Rashid (My University, 2022)
The aim of this survey-based quantitative study was to examine the relationship between 221 preservice preschool teachers’ views about Gordon’s Teacher Effectiveness Training (TET) model and their communication skills. Also, their views about the TET and their communication skills were examined based on their demographic characteristics. Data were collected through a demographic information form, the Discipline Strategies Questionnaire, and the Communication Skills Scale with the approval of Social and Humanities Research and Publication Ethics Committee of Van Yüzüncü Yıl University (Date: 01/10/2020; Number: 2020/10-04). This revealed that the views of the female preservice teachers about the TET model were more positive than those of their male colleagues, and that the former group’s communication skills were also better – reflecting the generally positive relationship between the respondents’ views of the TET model and their communication skills. However, neither TET views nor communication skills varied significantly by age group. Results show that for preservice teachers to put this style of classroom management into practice, they should be given more opportunities to gain classroom-management experience.